PERAN GURU DALAM MENCIPTAKAN PEMBELAJARAN LITERASI MATA PELAJARAN BAHASA INDONESIA DI KELAS V SD NEGERI 050718 CEMPA - Elfi Lailan Syamita Lubis (LPPM STKIP AL MAKSUM, 2019)
The study aims to know the role of the teacher in creating literacy in Bahasa Indonesia lesson. This research uses the interview technique and observation. The respondent of the study is the teacher that teaches in the 5th grade of SD Negeri 050718 Cempa. The method of data analysis in this research is descriptive qualitative, in which the kind of data is explanation and documentation. The data is gained and analyzed by using descriptive qualitative. Based on the interview shows that there are obstacles in the school, such as school planning in creating literacy is not implementable and the source is not complete as the material in Bahasa Indonesia lesson. The teacher spends all his energy by creating and posting the book at the edge of the classroom so that the students may read books every time. Meanwhile, based on the observation at the classroom, the researcher finds some books are posted by the teacher in the classroom whiteboard that are full of books related to the knowledge.